Universal equivalent static wind loads of fluctuating wind loads on large-span roofs based on compensation of structural frequencies and modes. (August 2020) - Sun, Wuyi; Zhang, Qinghua
Abstract: On the basis of a wind tunnel test of the structural rigid model, this paper first calculates the target responses (TRs) of the fluctuating wind loads which are used to compute the universal equivalent static wind loads (UESWLs) of a linear complex large-span roof. Via the linear combination of multiple-order structural mode inertial forces (MOSMIFs), the uncompensated UESWL method of a few lower-order frequencies and modes is then presented. This, however, incurred considerable errors. Therefore, according to the response differences between the accurate TRs and the corresponding UESWL-induced responses (UESWL-IRs) by the uncompensated UESWLs, a new compensated UESWL method is proposed by compensating structural frequencies and modes to eliminate or lessen the errors in the uncompensated UESWL method. Finally, the two methods are applied to a linear complex large-span roof. The computations show that the compensated UESWL method has the clear physical meaning, high accuracy and wide applicability, and it owns an application potential for large-span roofs as well as other structures.